Clinical features of the course of tuberculous meningitis in HIV-infected patients - Irina Y. Babaeva; Andrey I. Shevchenko; Diana V. Dudchenko; Christina A. Tolochko; Victor V. Romantsov; Egor O. Nartov (Consilium Medicum, 2023)
Background. Central nervous system tuberculosis is one of the most severe forms of extrapulmonary tuberculosis, which is due to an unfavorable clinical course, a high incidence of neurological complications and deaths. Despite this, the problem of early diagnosis is still not solved.